2023
DOI: 10.1186/s12911-023-02274-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural network in daily prediction of bleeding in ICU patients treated with anti-thrombotic therapy

Daonan Chen,
Rui Wang,
Yihan Jiang
et al.

Abstract: Objectives Anti-thrombotic therapy is the basis of thrombosis prevention and treatment. Bleeding is the main adverse event of anti-thrombosis. Existing laboratory indicators cannot accurately reflect the real-time coagulation function. It is necessary to develop tools to dynamically evaluate the risk and benefits of anti-thrombosis to prescribe accurate anti-thrombotic therapy. Methods The prediction model,daily prediction of bleeding risk in ICU p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Overall, only 10 studies were identified, and are summarized in Supplementary Table S3 (available in the online version). 69 70 71 72 73 74 75 76 77 78 Two studies predicted PTS with good to excellent performance (AUC: 0.83–0.89) 69 70 The diagnosis of PTS was based on the Villalta score, but immediate comparison with the score was not performed. Regarding prediction of mortality, one shortcoming is the variability of its definition between studies, in terms of time to event.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, only 10 studies were identified, and are summarized in Supplementary Table S3 (available in the online version). 69 70 71 72 73 74 75 76 77 78 Two studies predicted PTS with good to excellent performance (AUC: 0.83–0.89) 69 70 The diagnosis of PTS was based on the Villalta score, but immediate comparison with the score was not performed. Regarding prediction of mortality, one shortcoming is the variability of its definition between studies, in terms of time to event.…”
Section: Resultsmentioning
confidence: 99%
“…In cardiovascular diseases (CVDs), plaque accumulates in the coronary artery and affects blood flow, resulting in a lack of oxygen or nutrition in the heart that can lead to death. The American Heart Association annually releases statistical reports on heart disease, stroke, and cardiovascular risk factors, and considerable research efforts are devoted to CVD. , This focus includes artificial polymer bypass graft transplants, , stent material innovations, antithrombosis medicine studies, , tissue engineering for artificial vascular grafts, ,, tissue repair medicine for ischemia, , and creating biomarkers for detection. ,,, …”
mentioning
confidence: 99%